Legal Protection in Land Acquisition for Public Interest: A Dilemma Between State Regulation and Social Welfare - Irawan, Armalia Berlinda; Subekti, Rahayu; Sobirov, Bobur Baxtishodovich (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2024)
The development of infrastructure for the general interest in Indonesia continues to be encouraged by the Government to improve the general well-being, but it has to deal with public ownership by acquiring land for such development. This study determines the forms of legal protection for landowners affected by land acquisition. The study uses normative legal research, which compares legal issues in two countries, Indonesia and the Netherlands. This research is descriptive, using statute, conceptual, and case approaches. The results of this study show that legal protection for landowners affected by land acquisition in Indonesia, based on some cases in the investigated judgment, needs to protect and provide legal certainty for landowners fully. The case is based on unilaterally granting compensation, and the court has not filed a lawsuit for such compensation. The courts in Indonesia, in settling the land acquisition damages dispute, are more subject to existing rules that do not look at the situation on the ground. The implementation of the acquisition process carried out by the Evaluation Team must comply with the procedures in the land acquisition regulations. Secondly, legal protection for landowners affected by land acquisition in the Netherlands; based on several cases in the ruling under investigation, the Netherlands has provided legal protection in the form of high compensation for the cost of landowner losses. The Supreme Court is working hard for a reasonable outcome by providing high-value compensation. Both states have the same obstacle in implementing land acquisition: a dispute with landowners about compensation.